Varedeklaration i ordbøger? - Møller, Bernt (Nordiske Studier i Leksikografi, 1997)
The present article focuses on "the dictionary selector" as opposed to the dictionary user. It briefly discusses the notion of quality in relation to the assumed needs of the selector. Inspired by the principle and practice oflnfonnative Labelling, the insertion on the back ofthe dictionary ofa "User’s Guide" is recommended. The required items ofinformation ofthe User’s Guide as well as their presentation are discussed.